Observing the user experience : a practitioner's guide to user research - Kuniavsky, Mike.; Goodman, Elizabeth; Moed, Andrea (Amsterdam : Morgan Kaufmann, 2012)
The gap between who designers and developers imagine their users are, and who those users really are can be the biggest problem with product development. Observing the User Experience will help you bridge that gap to understand what your users want and need from your product, and whether they'll be able to use what you've created. Filled with real-world experience and a wealth of practical information, this book presents a complete toolbox of techniques to help designers and developers see through the eyes of their users. It provides in-depth coverage of 13 user experience research techniques that will provide a basis for developing better products, whether they're Web, software or mobile based. In addition, it's written with an understanding of how software is developed in the real world, taking tight budgets, short schedules, and existing processes into account. Explains how to create usable products that are still original, creative, and unique. A valuable resource for designers, developers, project managers-anyone in a position where their work comes in direct contact with the end user. Provides a real-world perspective on research and provides advice about how user research can be done cheaply, quickly and how results can be presented persuasively. Gives readers the tools and confidence to perform user research on their own designs and tune their software user experience to the unique needs of their product and its users.
Includes bibliographical references (p. 571-576) and index.
Keywords: User-centered system design; Observation (Scientific method)